The Influence Of Social Media Marketing, Brand Image And Product Quality On Purchasing Decisions At PT Velindo Tours And Travel - Dinda Rindana; Yana Diana; Annisa Sanny (Jurnal Fokus Manajemen, 2026)
The research analysis aims to analyze social media marketing, brand image, and product quality on purchasing decisions at PT Velindo Tours and Travel. The data analysis technique used was an associative research method with the help of SPSS version 25. This study employed multiple linear regression analysis. The sample size was 72 respondents. Primary data collection used a questionnaire. The results showed that social media marketing had a positive and partially significant effect on purchasing decisions at PT Velindo Tours and Travel. Brand image had a positive and partially significant effect on purchasing decisions at PT Velindo Tours and Travel. Product quality had a positive but partially insignificant effect on purchasing decisions at PT Velindo Tours and Travel. Social media marketing, brand image, and product quality had a positive and significantly simultaneous effect on purchasing decisions at PT Velindo Tours and Travel.